AN ANALYSYS OF CONVERSATIONAL IMPLICATURE IN PODCAST DEDDY CORBUZIER’S YOUTUBE - Jasmir, Rini Afrilesa; Sartika, Winda; Magria, Vera (Universitas PGRI Sumatera Barat, 2021)
This Research is a study of pragmatics to identify types and Meaning and Functions of conversational implicature, especially participants utterances based on context that used in Deddy Corbuzier podcast on youtube. This thesis applied descriptive qualitative research in which the data are obtained from conversation Deddy corbuzier podcast. The data are collected by observational method support by downloding and note-taking technique. Data analysis is conducted by referential identity method. The result of analysis is presented by formal and formal method.The result of the analysis shows that guest star utterances in deddy corbuzier podcast contain three types on conversational implicature. The first, Generalized conversational implcature, it is an implicature that does not need context to assume the utterance. The second, Particularized conversational implicature, it is an implicature that can be assumed via knowing the specific context and also needs special knowledge of the listener. The third, scale implicature, it is a implicature that communicated through the using a word that contain a scale of values, such as identifying a quantity ( all, most, many, some, few). For addition, from 15 utterances that found, 6 utterances categorized as particularized conversational implicature, 3 utterances categorized generalized conversational implicature and 2 utterance categorized as scale implicature. There are four functions of implicature indicated. They are (1) Asserive (9) (2) Directives (2) (3) Declarative (1) (4) Expressive functions (2). Assertives function dominantly occur in podcast deddy corbuzier’s youtube. This is caused by the presention of explaination.